ANALISIS KESEPADANAN PENERJEMAHAN IDIOM MANGA “BARAKAMON” VOLUME 1-5 KARYA SATSUKI YOSHINO TERJEMAHAN ELEX MEDIA KOMPUTINDO - Syifa Az Zahrah, Sabita; Muhammad Ali, Hamdi; Yuniarsih (Universitas Airlangga, 2025)
This research aims to identify the manifestation of idioms and the Equivalent strategies eploed by the translator in the manga Barakamon (volume 1-5) from Japanese into Indonesian. The analysis of idiom Equivalent strategies was conducted through four comprehensive levels: above word level, grammatical, textual, and pragmatic. Utilizing contextual and semantic analysis, the study identified a total of 47 idioms within the source text. The findings reveal that the manifestation of idioms is dominated by metaphorical expressions rooted in psychological and anatomical elements. Linguistically, these idioms tend to undergo shifts toward more functional and pragmatic meanings in the Indonesian translation. Based on the frequency of Equivalent strategies, the pragmatic level emerged as the most dominant (28), followec by above word level (18), grammatical (18), adn textual (9). This phenomenon underscores that the translator prioritizes dynamic Equivalent, naturalness, and contextual suitability within the target culture over preserving the lexical forms of the source language. This approach ensures that the emotional and cultural nuances of the manga are accurately conveyed to the local audience.